1999
DOI: 10.1002/(sici)1521-3838(199912)18:6<561::aid-qsar561>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

A Three Binding Site Hypothesis for the Interaction of Ligands with Monoamine G Protein-coupled Receptors: Implications for Combinatorial Ligand Design

Abstract: Three-dimensional models of ligand-receptor complexes based on site-directed mutagenesis experiments of the monoamine G protein-coupled receptors reveal the existence of three distinct drug binding sites inside the receptors. Here, we develop this``three-site'' hypothesis and outline its implications for the modular design of ligands for monoamine GPCRs. Molecular models of receptor-ligand complexes are built for the 5-HT 1A receptor where mutagenesis studies map three spatially distinct binding regions which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 22 publications
3
27
0
Order By: Relevance
“…A binding pocket was easily identified on the extracellular side of the structure, allowing the 5-HT amine moiety to interact with Asp-116 in TM3 and its hydroxyl moiety to interact with Ser-199 in TM5; both in good agreement with experimental data (41,42). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A binding pocket was easily identified on the extracellular side of the structure, allowing the 5-HT amine moiety to interact with Asp-116 in TM3 and its hydroxyl moiety to interact with Ser-199 in TM5; both in good agreement with experimental data (41,42). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, according to the so-called three-binding site hypothesis, amine ligands bind at three spatially distinct binding regions, all of which are supposed to be located between the seven helix transmembrane domains of the amine GPCRs. Moreover, depending on ligand size and shape of the ligand, the binding is proposed to more or less overlap these three binding regions (Jacoby et al, 1999). Obviously, as the hypothesis is based on 3D modeling, it is restricted to the correctness of the docking procedures.…”
Section: Proteochemometrics Modeling Of G-protein Coupledmentioning
confidence: 89%
“…The picture emerging from these studies is also not entirely clear and sometimes even quite contradictory; e.g., modeling and mutagenesis studies suggest the placement of the binding pocket of pirenzepine in alternative binding pockets of the muscarinic receptors (Fanelli et al, 1995;Bourdon et al, 1997) and it is not an easy tasks to resolve such ambiguities using 3D modeling. It has also been suggested that antagonist ligands for amine receptors may bind to alternative binding pockets in the receptors (Schwartz 1994;Jacoby et al, 1999). Thus, according to the so-called three-binding site hypothesis, amine ligands bind at three spatially distinct binding regions, all of which are supposed to be located between the seven helix transmembrane domains of the amine GPCRs.…”
Section: Proteochemometrics Modeling Of G-protein Coupledmentioning
confidence: 92%
See 1 more Smart Citation
“…For the monoamine GPCRs, a three-bindingsite hypothesis [2] was recently demonstrated by combining: 1) analyses of the architectures of known monoamine GPCR ligands; 2) analyses of molecular models of the ligandreceptor interactions; and 3) structural bioinformatics analyses of the sequence similarities of the three distinct binding regions of ''one-site-filling'' ligand fragments within the monoamine GPCR family. For the 5HT 1A receptor, which provided a frame for the discussion of other related ligand-GPCR interactions, mutagenesis studies map three spatially distinct binding regions which correspond to the binding sites of the ''small, one-site-filling'' ligands 5-HT, propranolol and 8-OH-DPAT, respectively ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%